2019
DOI: 10.21608/jbaar.2019.105884
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of rosemary extract against Etoposide induced liver toxicity, injury and KI67 alterations in rats

Abstract: Etoposide is chemotherapeutic drugs that inhibit topoisomerase II activity and long been used for the treatment of human malignancies. The present study was designed to investigate the possible protective effect of rosemary extract against Etoposide-induced liver toxicity, injury, and KI67 alterations in rats. A total of 40 male Wister albino rats were divided randomly into four groups (1 st group was control; 2 nd group was treated with rosemary, 3 rd group was received Etoposide, and 4 th group was treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…Compared to control rats, etoposide therapy resulted in a significant increase in serum ALT, AST, and ALP, as well as a significant drop in albumen and total proteins, indicating liver injury. This finding is consistent with the findings of Nasr (2013), Al-Ameri (2017), Almakhatreh et al (2019, who reported that etoposide administration significantly increased the levels of ALT, AST, and ALP, as well as a significant decrease in albumen and total proteins in the serum, all of which are consistent with liver toxicity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to control rats, etoposide therapy resulted in a significant increase in serum ALT, AST, and ALP, as well as a significant drop in albumen and total proteins, indicating liver injury. This finding is consistent with the findings of Nasr (2013), Al-Ameri (2017), Almakhatreh et al (2019, who reported that etoposide administration significantly increased the levels of ALT, AST, and ALP, as well as a significant decrease in albumen and total proteins in the serum, all of which are consistent with liver toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…Bile duct proliferation was also discovered. Similar changes were recorded by other investigators (Ravindra et al, 2012;Tousson et al, 2019). The production of free radicals is largely responsible for the enormous degenerative alterations produced by etoposide.…”
Section: Referencessupporting
confidence: 86%
“…Also, protein expression levels of α-SMA were decreased than TAA-moringa treated group. Our results agreed with Tousson et al, (2019). The protective effect of rosemary extract against TAA hepatotoxicity attributed to its richness in carnosic acid and rosmarinic acids which have antiinflammatory, anti-necrotizing and anti-fibrotic properties (Bahri et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…The present study was conducted to examine the ability of Tau to alleviate histopathological alterations in the liver and kidneys of rats treated with ETP. It has been demonstrated in a previous study that intraperitoneal injection of 1 mg/kg of ETP daily for four weeks induced hepatotoxicity evidenced by moderate atrophy and vacuolar degeneration of hepatocytes, pyknosis, marked cellular infiltrations, as well as marked congestion in hepatic veins (Tousson et al, 2019). These findings were in accordance with our results in which ETP administered intraperitoneally over a period of three days (14.7 mg/kg/day) for a total cumulative dose of 44 mg/kg and an observation period of 15 days resulted in hepatotoxicity characterized by congestion of hepatic blood vessels, chronic inflammatory cell infiltration predominantly lymphocytes, edema, vacuolar degeneration of hepatocytes, atypical cells, pyknosis of hepatocytes, and necrosis.…”
Section: Discussionmentioning
confidence: 95%